National assessment and planning for improved fish handling in Solomon Islands - Batalofo, Margaret; Hunnam, Kimberly; Buga, Ben; Akao, Ivory; Tua, Paul; Gereniu, Collin; Jino, Luke; Solo, Madeline; Wate, Jillian Tutuo; Siota, Faye Aborina; Notere Boso, Delvene; Saeni-Oeta, Janet; et al. (WorldFish, 2023)
The report summarizes the discussions and interviews with provincial fisheries officers (PFOs) at the annual PFO conference in Honiara, November 23, 2022.The report also identifies the next steps needed to build a program on fish handling based on input from participants at the Fish Innovation project reflection workshop in Nusatupe, May 16–19, 2023.